Neuromuscular characteristics and fatigue during 10 km running - Paavolainen, L; Nummela, A.; Rusko, H.; Hakkinen, K. (International Journal of Sports Medicine, 1999)
This study investigated neuromuscular characteristics and fatigue during 10 km running (10 K) performance in well-trained endurance athletes with different distance running capability. Nine high (HC) and ten low (LC) caliber endurance athletes performed the 10 K on a 200 m indoor track, constant velocity lap (CVL, 4.5 m x s(-1)) 5 times during the course of the 10 K and maximal 20 m speed test before (20 m(b)) and after (20 m(a)) the 10 K. Running velocity (V), ground contact times (CT), ground reaction forces (F) and electromyographic activity (EMG) of the leg muscles (vastus lateralis; VL, biceps femoris; BF, gastrocnemius; GA) were measured during 20 m(b), 20 m(a), and CVLs. The 10 K times differed (p<0.001) between HC and LC (36.3+/-1.2 and 39.2+/-2.0 min, respectively) but no differences were observed in 20 m(b) velocity. The 10 K led to significant (p<0.05) decreases in V, F and integrated EMG (IEMG) and increases in CTs of 20 m(a) in both groups. No changes were observed in HC or LC in F and IEMG during the CVLs but HC showed shorter (p<0.05) mean CT of CVLs than LC. A significant correlation (r = -0.56, p<0.05) was observed between the mean CT of CVLs and velocity of 10 K (V10K). Pre-activity of GA in relation to the IEMG of the total contact phase during the CVLs was higher (p<0.05) in HC than LC. The relative IEMGs of VL and GA in the propulsion phase compared to the IEMG of the 20 m(b) were lower (p<0.05) in HC than LC. In conclusion, marked fatigue took place in both HC and LC during the 10 K but the fatigue-induced changes in maximal 20 m run did not differentiate endurance athletes with different V10K. However, a capability to produce force rapidly throughout the 10 K accompanied with optimal preactivation and contact phase activation seem to be important for 10 km running performance in well trained endurance athletes.